Letter to Jane Tolmach from Jack Howard - Jack Howard:::::: (1961)
A letter to Jane Tolmach from Jack Howard. The letter discusses his efforts to return a tape that Jane loaned him in person but schedule conflicts had prevented him from doing so. The tape was mailed along with the letter.